Feasibility, Safety, and Exploratory Outcomes of Methylphenidate for Posttraumatic Stress Disorder Among Patients With Ischemic Stroke - Chaitali Dagli; Charity J. Morgan; Lori L. Davis; Chen Lin (The International Journal of Psychiatry in Medicine, 2026)
Objective Posttraumatic stress disorder (PTSD) is prevalent among veterans and is associated with increased stroke risk. This study examined the feasibility, safety, and preliminary efficacy of methylphenidate (MPH) for reducing PTSD symptom severity and improving functional outcomes among veterans with pre-existing PTSD recovering from stroke. Methods A randomized, double-blind, placebo-controlled phase 2 pilot trial was conducted at a Veterans Affairs medical center. Veterans aged 40-75 years with ischemic stroke and pre-existing PTSD were randomized 1:1 to receive MPH or placebo for 12 weeks followed by a 2-week taper. The outcomes included clinician-rated PTSD symptom severity using the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5), self-reported PTSD symptoms with the PTSD Checklist for DSM-5 (PCL-5), global functional disability via the modified Rankin Scale (mRS), and stroke-related quality of life and function measured by the Stroke Impact Scale–16 (SIS-16). Between-group differences in change scores were evaluated using two-sample tests. Results Twenty veterans were enrolled (mean age 63.7 years; 95% male). Baseline characteristics were similar between treatment groups. CAPS-5 and PCL-5 scores decreased over time in both groups, with no significant between-group differences, although greater reductions were observed in the MPH group at multiple time points. Both groups demonstrated modest improvements in functional outcomes, with trends toward greater gains in cognitive and participation-related domains among participants receiving MPH. MPH was generally well tolerated, with no unexpected safety concerns observed. Conclusion MPH was feasible and generally well tolerated. Exploratory analyses suggested possible improvements in selected cognitive and recovery-related domains that warrant confirmation in adequately powered studies.